Comparison Analysis Of Optimal Portfolio With The Capital Asset Pricing Model (CAPM) Before And During The Covid-19 Pandemic : Study on Liquid-45 Index Stock Period 2018-2021 - Usman, Usman (DAS Institute, 2022)
This study aims to compare the optimal portfolio composition of stocks, the proportion of funds in each stock, and calculate the return and portfolio risk on stocks that are included in the index of the liquid-45 (ILQ-45) before and during Covid-19 on the Indonesia Stock Exchange in the period May 2018 – December 2021. The research method uses a comparative description. The research sample using the purposive sampling method was obtained from the 30 stocks before Covid-19 and 35 shares during Covid from the index liquid-45 (ILQ-45). The results showed: 1.) an arrangement of the optimal portfolio using the CAPM before the Covid-19 pandemics on the LQ45 index with 30 stock varieties shows that none of the stocks are included in the optimal portofolio category because the Expected return (E(Ri) CAPM and Excess Return to Beta (ERB) value results are both negative. These are greatly influenced by the Return Market (Rm) that has a negative value, while the arrangement of the optimal portfolio during Covid-19 on the LQ45 index with 35 sample stocks is that 14 stocks fall into the category optimal portfolio. 2.) The results from the optimal stock portfolios before and during Covid-19 cannot be compared